An Analysis of the Current Situation of Chinese University Students’ English Reading Self-efficacy and A Proposed Intervention Program for Enhancement - ZHENG, Rui (Pacific International Journal, 2023)
China attaches great importance to the development of English language learning and education, and English language education is still in the process of continuous exploration and improvement. Improving students’ English reading self-efficacy to enhance their English reading is an attempt to enhance students’ English reading from the perspective of non-linguistic factors. Taking a Chinese university (Hunan University of Science and Engineering, HUSE) as an example, a questionnaire survey and data analysis on university students’ English reading self-efficacy found that: The university students are generally at a medium level in English reading self-efficacy. Guaranteeing students’ time investment in reading, improving students’ reading materials, strengthening of strategic guidance for students’ reading, improving students’ reading style, strengthening teachers’ guidance on attribution of students’ reading failures and on praising students for successful reading events are the proposed intervention program for enhancement of English reading self-efficacy.